Reply to Hansen and Lieberman - van den Berg, Willem H. (Journal of Scientific Exploration, 2015)
<!--[if gte mso 9]> 14.00 <![endif]--> It is indeed interesting that the non-classical behavior of the pendulum persists after the human subject has departed. We did observe this, but generally not for as long as reported by H&L. <span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; color: #222222; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->